Grid cyber security: secure by design, continuous threat monitoring, effective incident response and board oversight. Issue 6 (June 2021) - Geach, Dale
Abstract : Grids are possibly the highest expression of engineering serving society. From the aqueducts created in the sixth century BCE to the modern era birth of gas utilities in the 1820s, followed by electricity generation and distribution grids in the 1880s and the computer information-sharing age kicking off in the 1960s, we have been creating distribution infrastructure. Grids are possibly the highest expression of engineering serving society. We have lots of infrastructure, spanning generations of engineering and technology, still in service. This presents a problem as there are many who see these grids as vulnerable and high-value targets. Dale Geach of Siemens UK examines where the weaknesses lie and how they have already been exploited. As grid operators seek the huge benefits of modernising grid operations, it's important that they adopt a secure-by-design network with continuous threat detection and watertight response plans.